Early undergraduate research experience at Makerere University Faculty of Medicine: a tool for promoting medical research - Munabi, I G (Makerere Medical School, 2006)
BACKGROUND: Research is one of the key distinguishing features of an academic institution. The way an institution grooms its future researchers determines its long term survival. The ability to do and communicate ones research findings is so important that it is now an internationally recognized minimum competency for graduate of any medical school. To remain relevant the Faculty of Medicine Makerere University needs to identify research enhancing opportunities like undergraduate research experiences. METHODS: This was a cross sectional study involving 424 graduate and undergraduate students of Makerere University Medical School on the traditional curriculum. A self administered questionnaire was used to capture reported details of individual research experiences. RESULTS: There were 424 student respondents, 88% of whom were undergraduates (372/424). About 41% (176/424) of these respondents reported having had a previous research experience. Among the postgraduates 74% (37/50) reported having had a previous research experience compared with 68% (139/342) of the undergraduates [OR=4.16, 2.07–8.57]. The sum of individual undergraduate experiences had the strongest positive correlation with the total number of studies done by an individual [R=0.801]. CONCLUSION: Early, guided undergraduate research experience can be used to promote research within the Faculty of Medicine Makerere University.